The Effectiveness of Melati Book Program to Improve Healthy Behavior and Reduce Blood Pressure in Hypertensive Patients at Sidorejo Kidul Community Health Center in Salatiga - Ony Suciati; Didik Gunawan Tamtomo; Prawito Prawito (Journal of Health Promotion and Behavior, 2020)
Background: 319 cases of hypertension patients occurred in the community health center in the last 2 years throughout 2019 and 256 cases up to March 2020. Therefore, fighting hypertension was one of the main programs at Sidorejo Kidul Community Health Center. This program was realized by publishing and distributing Melati Book or Books Against Hypertension to hypertension patients. However, the hospital has never conducted a study on whether the distribution of the Melati Book was effective in fighting hypertension in patients in Sidorejo Kidul Community Health Center.Subjects and Method: The study method was Quasi-experiment. This study used a random-number method to obtain the sample. A sample of 150 hipertensive patients was classified into 2 groups: 75 patients were in the intervention group and 75 other patients were in the control group. The data were analyzed by t-test.Results: After intervention, mean score of healthy behavior in the intervention group (Mean= 3.57; SD= 0.10) was higher than the control group (Mean= 0.49; SD= 0.19) and it was statistically significant (p<0.001). After intervention, mean score of systolic blood pressure in the intervention group (Mean= -32.59; SD= 1.02) was lower than the control group (Mean= -6.83; SD= 1.02) and it was statistically significant (p<0.001).Conclusion: Melati book can be used to improve the healthy behavior and reducing blood pressure in hypertensive patients at Sidorejo Kidul Community Health Center in Salatiga.Keywords: melati book, healthy behavior, decrease in blood pressureCorrespondence: Oni Suciati. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: onysuciati975@gmail.com. Mobile: 081327073562.Journal of Health Promotion and Behavior (2020), 06(04): 264-271https://doi.org/10.26911/thejhpb.2020.05.04.04.